Seasonality alters drivers of soil enzyme activity in subalpine grassland soil undergoing climate change. (September 2018) - Puissant, Jérémy; Jassey, Vincent E.J.; Mills, Robert T.E.; Robroek, Bjorn J.M.; Gavazov, Konstantin; De Danieli, Sebastien; Spiegelberger, Thomas; Griffiths, Robert; Buttler, Alexandre; Brun, Jean-Jacques; Cécillon, Lauric
Abstract: In mountain ecosystems with marked seasonality, climate change can affect various processes in soils, potentially modifying long-term key soil services via change in soil organic carbon (C) storage. Based on a four-year soil transplantation experiment in Swiss subalpine grasslands, we investigated how imposed climate warming and reduced precipitation modified the drivers of soil carbon enzyme potential activities across winter and summer seasons. Specifically, we used structural equation models (SEMs) to identify biotic (microbial community structure, abundance and activity) and abiotic (quantity and quality of organic matter resources) drivers of soil C-enzymes (hydrolase and oxidase) in two seasons under two different climate scenarios. We found contrasting impacts of the climate manipulation on the drivers of C-enzymes between winter and summer. In winter, no direct effect of climate manipulation (reduced rainfall and warming) on enzyme activity was observed. Yet, climate indirectly down-regulated enzyme activity through a decrease in the availability of water extractable organic carbon (WEOC) labile resources. During summer, reduced soil moisture –induced by the climate manipulation– directly reduced soil microbial biomass, which led to a decrease in C-enzyme activity. In general, across both seasons, neither microbial community structure, nor organic matter quality were strong determinants of enzymatic activity. In particular organic matter recalcitrance (aromaticity) was not found as a general driver of either hydrolase or oxidase C-enzyme potential activities, though we did observe higher C-enzyme activities led to an increase of particulate organic matter recalcitrance in the summer season. Overall, our results highlight the seasonality of climate change effects on soil organic matter enzymatic decomposition, providing a comprehensive picture of seasonal potential cause and effect relationships governing C mineralization in subalpine grasslands. Highlights: Contrasting impacts of the climate manipulation on the drivers of carbon enzymes between winter and summer. In winter, the reduced availability of water extractable organic carbon downregulated enzyme activity. In summer, reduced soil microbial biomass led to a decrease of C-enzyme activity.